The use of videoconference in international judicial and extrajudicial proceedings: Challenges for private international law - Baltar, Leandro L; Scotti, Luciana B. (Revista Tribuna Internacional, 2021)
The advances and achievements of technology have a direct impact on the legal world. In recent decades, the effects of technology can be found within Private International Law (DIPr), especially in matters related to improving or streamlining processes. However, its regulation is on a slow and new path.Among them, we find videoconferencing as a tool capable of generating a large number of advantages that can well be taken advantage of in judicial and extrajudicial procedures in order to achieve effective international legal cooperation.The use of videoconferencing leads us to make some questions and reflections, among them the way in which this situation influences the law and the fulfillment of the judicial and extrajudicial function. We will seek in this work to analyze the incidence of new technologies in the DIPr, especially, the use of videoconferencing in both judicial and extrajudicial processes.